2020
DOI: 10.1097/yco.0000000000000645
|View full text |Cite
|
Sign up to set email alerts
|

Emerging trends in eating disorders among sexual and gender minorities

Abstract: Purpose of review-To review the recent literature on eating disorders, disordered eating behaviors, and body image dissatisfaction among sexual and gender minority populations, including, but not limited to, gay, lesbian, bisexual, and transgender people.Recent findings-Overall, eating disorders, disordered eating behaviors, and body dissatisfaction are common among sexual and gender minority populations. Lifetime prevalence for anorexia nervosa (1.7%), bulimia nervosa (1.3%), and binge-eating disorder (2.2%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
109
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 181 publications
(133 citation statements)
references
References 30 publications
(41 reference statements)
4
109
0
Order By: Relevance
“…Similarly, transgender women previously reported higher scores on the Shape Concern subscale than presumed cisgender women [20]. Shape concerns in genderexpansive individuals may be linked to gender dysphoria and body dissatisfaction when one's body shape is discrepant from one's gender identity [18,37,38]. It may be especially challenging for gender-expansive individuals to attain certain shape ideals when certain anatomic structures cannot be altered medically or surgically [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, transgender women previously reported higher scores on the Shape Concern subscale than presumed cisgender women [20]. Shape concerns in genderexpansive individuals may be linked to gender dysphoria and body dissatisfaction when one's body shape is discrepant from one's gender identity [18,37,38]. It may be especially challenging for gender-expansive individuals to attain certain shape ideals when certain anatomic structures cannot be altered medically or surgically [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Additional supplemental analyses (results stratified by year and BMI) are displayed in the online supplement. All analyses were conducted in 2021 using Stata 15.1 [53].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of eating disorders and disordered eating amongst LGBT adults and adolescents found these groups were at greater risk than the general population, identifying a heightened risk among gay men, bisexuals and trans people, with mixed results for lesbian adults and adolescents. (7) Although a previous study comparing lesbian adolescents to their heterosexual peers identified a greater prevalence of purging behaviours and focus on reducing weight among the lesbian cohort (8). Eating disorders and disordered eating can be prominent among gay males due to the cultural pressures within the community to fit certain body type categories.…”
Section: Mental Healthmentioning
confidence: 99%
“…(8) Factors suggested to contribute to the development of eating disorders for LGBT people include increased stress through experiences of stigma and violence but also cultural ideals within the LGBTQ+ community, such as the need to be 'thin' and 'fit' to be viewed as attractive. (7,8) For substance use disorders, evidence is limited. While many studies have identified heightened levels of substance use/abuse among LGBT groups along with high risk factors for developing a disorder, very few have examined substance disorders specifically.…”
Section: Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation